Effect of ageing on the calibration of ballistic gelatin. Issue 4 (27th February 2018) - Guey, Jason; Rodrigues, S; Pullen, A; Shaw, B; Kieser, D C
Abstract : Purpose: Ballistic gelatin is commonly used as a validated surrogate for soft tissue during terminal ballistic testing. However, the effect of a delay between production and testing of a gelatin mould remains unknown. The aim of this study was to determine any potential effects of ageing on ballistic gelatin. Methods: Depth of penetration (DoP) of 4.5 mm spherical fragment simulating projectiles was ascertained using mixtures of 10%, 11.25% and 20% Type A 250 Bloom ballistic gelatin. Testing was performed daily for 5 days using velocities between 75 and 210 m/s. DoP at day 5 was statistically compared with day 1, and net mass change was recorded daily. Results: No significant difference was found for DoP observed with time in any of the samples (P>0.05). Spearman correlation was excellent in all moulds. The moulds with known standard calibrations remained in calibration throughout the study period. Mass loss of less than 1% was noted in all samples. Conclusion: Mass loss was the only quantifiable measure of changes in the blocks with time, but did not correlate with any changes in DoP. This may provide reassurance when undertaking such testing that an inadvertent delay will not significantly alter the penetration properties of the mould. Future research is recommended to determine any potential effect on the mechanical properties of gelatin at higher velocity impacts and whether the calibration corresponds to an adequate simulation under such conditions.